KOMUNIKASI FASHION DALAM KEBAYA ENCIM DAN BATIK PERANAKAN TIONGHOA: SOSIALISASI DAN DIFERENSIASI - Budianto, Erica Rachel; Bahaduri, Berti Alia; Rismantojo, Sandy (Universitas Mercu Buana, 2023)
Fashion, clothing and culture are communication and cultural phenomenon, in which fashion communication has both socialization and differentiation function. In the realm of fashion and clothing, the forming of social groups and personal identities are established through continuous communication process. This phenomenon occurred in the development of kebaya encim and Chinese Peranakan batik at Java in the 19th century. Kebaya encim was a type of kebaya worn by Peranakan Chinese women, therefore it had visual characteristics which were eminently influenced by Chinese culture. The Chinese Peranakan women used to wear kebaya as upper clothes, combined with Peranakan Chinese batik cloth as skirt At the beginning, kebaya encim and Peranakan Chinese batik emulated the kebaya and batik characteristics worn by Dutch women in Java. This was due to the desire of Peranakans to acquire equal privilidge with the Dutch in the society.This research aims to define the role of fashion communication in the development of kebaya encim and Peranakan Chinese batik in the 19th century at Java Island. Therefore, this research utilises descriptive qualitative approach. Theories which are used in this research are Barnard's fashion communication theory and Lukman's mimicry and hibridity theory. This research confirms that there is fashion communication process that can be emphasized from socialization and differentiation function with mimicry and hybridity phenomenon in kebaya encim and Peranakan Chinese batik. Socialization can be seen from mimicry of Dutch's kebaya and batik style to obtain social equality. Moreover there is also differentiation function, since the Chinese Peranakans made some special adjustments toward their own kebaya and batik characteristics in order to be more suitable with their culture.